Line-of-sight stability in unmanned aerial vehicle relays for hybrid free-space optical and visible light communication links under atmospheric effects - Maha Sliti; Salman Ghafoor; Sarra Ayouni; Manel Mrabet; Lassaad Ben Ammar; Muhammad Ijaz (PLoS ONE, 2026)
Optical links supported by an unmanned aerial vehicle (UAV) must sustain gigabit-class throughput despite atmospheric attenuation, turbulence, and platform-induced pointing errors. Single-technology designs based on free-space optical (FSO) or visible light communication (VLC) often lack robustness under changing altitude and weather conditions. This paper proposes a hybrid FSO/VLC UAV relay and a unified analytical model that combines Beer–Lambert path loss, turbulence-induced scintillation, and pointing jitter, coupling an FSO backhaul to a Lambertian V1LC access channel with a finite receiver field of view (FOV). MATLAB-based results show that, under light desert dust (extinction κ ≈ 0.35 k m − 1 ), the FSO branch retains ≈ 70.5 % of the transmitted power at 1 km and ≈ 49.7 % at 2 km, compared to ≈ 81.9 % and ≈ 67.0 % in clear visibility ( κ = 0.2 k m − 1 ) and ≈ 49.7 % and ≈ 24.7 % in haze ( κ = 0.7 k m − 1 ). The VLC branch maintains a signal-to-noise ratio (SNR) of at least 30 dB when F O V ≤ 20 ∘ for altitudes below 150 m. For line-of-sight stability, with a receiver capture half-angle of 20 μ r a d , the alignment probability is ≈ 99.97 % at a root-mean-square (RMS) pointing jitter of 5 μ r a d (stabilized) versus ≈ 58.9 % at 15 μ r a d (weak/no-stabilization control). These results provide practical thresholds for robust hybrid relays, including visibility-aware switching between FSO and VLC and sub- 10 μ r a d stabilization to maintain high alignment probability for smart-city and emergency scenarios.